Long‐Term Impacts on Groundwater and Reductive Dechlorination Following Bioremediation in a Highly Characterized Trichloroethene DNAPL Source Area. Issue 3 (22nd June 2018) - Schaefer, Charles E.; Lavorgna, Graig M.; Haluska, Alexander A.; Annable, Michael D.
Abstract: High‐resolution soil and groundwater monitoring was performed to assess the long‐term impacts of bioremediation using bioaugmentation with a dechlorinating microbial consortium (and sodium lactate as the electron donor) in a well‐characterized trichloroethene (TCE) dense nonaqueous phase liquid (DNAPL) source area. Monitoring was performed up to 3.7 years following active bioremediation using a high‐density monitoring network that included several discrete interval multi‐level sampling wells. Results showed that despite the absence of lactate, lactate fermentation transformation products, or hydrogen, biogeochemical conditions remained favorable for the reductive dechlorination of chlorinated ethenes. In locations where soil data showed that TCE DNAPL sources persisted, local contaminant rebound was observed in groundwater, whereas no rebound or continuous decreases in chlorinated ethenes were observed in locations where DNAPL sources were treated. While ethene levels measured 3.7 years after active treatment suggested relatively low (2 to 30%) dechlorination of the parent TCE and daughter products, carbon stable isotope analysis showed that the extent of complete dechlorination was much greater than indicated by ethene generation and that the estimated first‐order rate constant describing the complete dechlorination of TCE at 3.7 years following active bioremediation was approximately 3.6 y–1. Overall, results of this study suggest that biological processes may persist to treat TCE for years after cessation of active bioremediation, thereby serving as an important component of remedial treatment design and long‐term attenuation.